Construct Validity of the Kessler Psychological Distress Scale (K-10) Instrument in the Elderly with Disabilities: Rasch Model Analysis - Lukman Hilfi; Mulya Nurmansyah Ardisasmita; Fauzura Nuril Mahra (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2025)
Aging contributes to functional decline and heightened psychological distress that affects the older adults’ quality of life. The World Health Organization (WHO) recommends the 10-item Kessler Psychological Distress Scale (K-10) for assessing psychological distress, however the Classical Test Theory (CTT)-based evaluation method has limitations. Item Response Theory (IRT), specifically the Rasch model, offers a more accurate method for measuring the instrument’ validity and reliability. This study examined the construct validity of the K-10 Indonesian version in older adults with disabilities. A cross-sectional method and secondary data from 321 elderly individuals (≥60 years) with disabilities in Bandung City, Indonesia, were used between August and February 2025. The Instrument’s construct validity of was analyzed by performing the Rasch model. A total of 315 responses were eligible for analysis. The K-10 showed an overall fit to the Rasch model (mean outfit MnSq = 1.03±0.27). Item C10 (“feel worthless”) was identified as misfitting (outfit MnSq >1.4; ZSTD >2), although no factor bias was detected. The explained variance reached 54.10%. Reliability indicators were strong, with a Cronbach’s alpha of 0.89 and a person separation index above 2. However, category functioning and targeting did not fully meet Rasch expectations. The correlation between K-10 and WHODAS 2.0 showed a moderate positive relationship, though it did not reach the criterion for convergent validity (r >0.6).  The Indonesian version of the K-10 has acceptable construct validity in a sample of older adults with disabilities in Bandung City, Indonesia.